2009
DOI: 10.1111/j.1439-0396.2008.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pre‐press solvent‐extracted cottonseed meal supplemented with exogenous enzyme and digestible lysine on performance, digestibility, carcass and immunity responses of broiler chickens

Abstract: The response of broiler chickens to two levels of endo-1,4-beta xylanase (EC 3.2.1.8) and endo-1,3-beta glucanase (EC 3.2.1.6) combination (with and without), three levels of digestible lysine (0.8%, 0.9% and 1.0% with the applicability of ideal protein concept) and two levels of cottonseed meal (CSM; 20% and 30%) were evaluated in 2 x 3 x 2 factorial arrangement. A total of 2448 male Hubbard broiler chicks were fed on practical vegetable-based mash diets having 2750 kcal metabolizable energy (ME) per kg and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Single enzymes such as xylanases and glucanases are mostly incorporated in poultry diets, representing more than 80% of the global carbohydrase market (Adeola & Cowieson, 2011). However, in this study, treating the canola-based diets did not improve feed intake, weight gain, or FCE, which agreed with the findings of Simbaya et al (1996), Meng & Slominski (2005), and Mushtaq et al (2007), who reported no effect of multi-carbohydrase enzyme in chickens fed CM-based diets. Additionally, Jia et al (2012) and Radfar et al (2017) found no improvement in broilers fed diets containing 150 g/kg of CM supplemented with carbohydrase enzyme.…”
Section: Discussionsupporting
confidence: 87%
“…Single enzymes such as xylanases and glucanases are mostly incorporated in poultry diets, representing more than 80% of the global carbohydrase market (Adeola & Cowieson, 2011). However, in this study, treating the canola-based diets did not improve feed intake, weight gain, or FCE, which agreed with the findings of Simbaya et al (1996), Meng & Slominski (2005), and Mushtaq et al (2007), who reported no effect of multi-carbohydrase enzyme in chickens fed CM-based diets. Additionally, Jia et al (2012) and Radfar et al (2017) found no improvement in broilers fed diets containing 150 g/kg of CM supplemented with carbohydrase enzyme.…”
Section: Discussionsupporting
confidence: 87%
“…For this purpose, cottonseed meal (CSM) has extensively been investigated and it has been shown to be a potential source of protein and a substitute for costly SBM in poultry diets [1][2][3]. This oilseed residue is highly rich in protein, with values between 41% and 44% crude protein (CP), depending on the degree of dehulling before oil extraction [4]. On the other hand, using this ingredient in poultry feeds presents a number of challenges and limitations, including high fibre content, presence of gossypol, and unbalanced amino acids, particularly a low content of lysine [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…This oilseed residue is highly rich in protein, with values between 41% and 44% crude protein (CP), depending on the degree of dehulling before oil extraction [4]. On the other hand, using this ingredient in poultry feeds presents a number of challenges and limitations, including high fibre content, presence of gossypol, and unbalanced amino acids, particularly a low content of lysine [1,4]. The amount of gossypol in CSM has been reported to vary from 0.03% to 0.2% [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher fiber content of the canola meal (Chibowska et al, 2000) resulted in lower energy content (Bell, 1993;NRC, 1994;Khajali and Slominski, 2012). The inclusion rate of canola meal in poultry diets is limited (Kocher et al, 2000), because of their anti-nutritional components which interfere with metabolism and growth, induced liver haemorrhages, lower digestibility of nutrients (Iji, 1999;Leeson and Summers, 2001;Nahas and Lefrançois, 2001;Jozefiak et al, 2004;Mushtaq et al, 2007;Min et al, 2009;Khajali and Slominski, 2012) increased leg problems, litter problems (Austin et al, 1999) and growth performance (Ibrahim et al, 1980;Martland and Butler, 1984;Pusztai, 1989;Iji, 1999;Leeson and Summers, 2001;Nahas and Lefrançoi, 2001;Jozefiak et al, 2004;Mushtaq et al, 2007;Min et al, 2009).…”
Section: Introductionmentioning
confidence: 99%